2019
DOI: 10.1111/jphp.13084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxicity and liver targeting of 3-O-β-D-Galactosylated Resveratrol

Abstract: Objectives Resveratrol (Res), a naturally occurring polyphenol, has shown pharmacological activities in treatment of liver diseases. However, the application of Res was limited by its poor bioavailability and liver targeting. Herein, 3‐O‐β‐D‐Galactosylated Resveratrol (Gal‐Res) was synthesized by structural modification of Res to enhance bioavailability and liver targeting. Methods The Gal‐Res was characterized by IR, 1H‐NMR spectra and MS. The in vitro antitumour experiments, in vivo pharmacokinetics and biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Resveratrol also reduced the pyrogallol-induced increase in the activity of the metabolizing enzymes CYP1A2 (cytochrome P450 1A2) and CYP2E1 (cytochrome P450 2E1) [137]. A recent study by Farghali et al [138] demonstrated that administration of resveratrol attenuated inflammation in d-galactosamine-sensitive and LPS-induced hepatitis [139]. This was highlighted by a reduction in TBARS (thiobarbituric acid reactive substances), AST, ALT, conjugated dienes, and bilirubin levels.…”
Section: Resveratrol In Chemical-induced Hepatotoxicitymentioning
confidence: 97%
“…Resveratrol also reduced the pyrogallol-induced increase in the activity of the metabolizing enzymes CYP1A2 (cytochrome P450 1A2) and CYP2E1 (cytochrome P450 2E1) [137]. A recent study by Farghali et al [138] demonstrated that administration of resveratrol attenuated inflammation in d-galactosamine-sensitive and LPS-induced hepatitis [139]. This was highlighted by a reduction in TBARS (thiobarbituric acid reactive substances), AST, ALT, conjugated dienes, and bilirubin levels.…”
Section: Resveratrol In Chemical-induced Hepatotoxicitymentioning
confidence: 97%
“…Aging models based on the administration of D-gal have been intensively utilized for validation of the antiaging efficacy of natural antioxidant compounds over the last decades [148]. In fact, the antioxidant properties of polyphenols have been tested in a number of studies using a model of skin aging based on the use of D-gal [149][150][151][152]. For instance, it was established that the combined treatment using resveratrol and calorie restriction restores hair condition, skin elasticity, and skin thickness in rats treated by D-gal [85].…”
Section: Natural Antioxidants and Polyphenols In Studies On D-gal-indmentioning
confidence: 99%
“…Currently, anticancer drugs are limited by weak selectivity towards tumour cells and severe side effects on normal tissues . Nano‐drug delivery systems, such as polymeric micelles, liposomes and nanoparticles (NPs), have been used to increase tumour targeting .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, anticancer drugs are limited by weak selectivity towards tumour cells and severe side effects on normal tissues. [1][2][3][4] Nano-drug delivery systems, such as polymeric micelles, liposomes and nanoparticles (NPs), have been used to increase tumour targeting. [5][6][7][8][9] NPs are known to enter tumour cells through the enhanced permeability and retention (EPR) effect due to their small size and large surface area.…”
Section: Introductionmentioning
confidence: 99%